The comparative method as a methodological component in public policies (Revista de Investigaciones Universidad del Quindío, 2020)
Objective. To expose the value of the comparative method as a base element for gestation, development and implementation of public policies in the various areas of government action. Method. Explain the meaning of the comparative method and its use as the main tool in academic (or research) works that are assigned to the subdiscipline of public policies. Result. It should be noted that the use of the comparative method is not limiting in the different areas of public policy. Conclusion. It is observed that case studies —one of the aspects of the comparative method— is more widely used in academic (or research) works; contrary to what happens in the formation of learners where the comparative method in its aspects (the case studies and case study) become relevant in the process of teaching and learning.
Keywords: public policies; comparative method; case studies; case study